Dry eye disease – how our lifestyle choices can affect the disease? - Dyrek, Martyna; Partyka, Aleksandra; Małachowski, Aleksander; Malinowski, Piotr; Błaszczak, Ewa; Kopczyńska, Urszula; Kopczyński, Cezary; Wójcik, Jakub; Gurdak, Kinga; Dydyk, Martyna (Journal of Education, Health and Sport, 2024)
Introduction: In today’s world, we know how important it is to keep healthy habits because many diseases begin with daily lifestyle choices. Dry eye disease is a disease of the ocular surface and there are many risk factors, that lead to developing this disorder. As the possible factors we can underline deficiency of vitamin D or Omega-3 fatty acids, lack of physical exercise, long screen time, or smoking tobacco. Aim of the study: This review seeks to highlight the issue of dry eye disease linked to everyday routines by examining clinical trial outcomes. Furthermore, it offers an analysis of potential strategies to prevent ocular alterations by critically evaluating the existing data. State of knowledge: The listed lifestyle choices cause a higher risk of developing dry eye disease and affect ocular health on many levels, leading to unpleasant feelings and affecting people’s lives. However, with some lifestyle changes, the risk of developing this disease can be decreased, and negative symptoms can be minimized. It is important to remember vitamin D, and Omega-3 supplementation, daily physical activity, minimalization of the time spent in front of the visual display terminals, and quitting smoking. Conclusions: Many daily habits are connected to developing dry eye disease, and it is very important to remember about the small daily changes, which can decrease the risk of the disease.